1992
DOI: 10.1108/02689239210017992
|View full text |Cite
|
Sign up to set email alerts
|

To Whom Do GPs Refer? A Study of the Development and Change of Referral Networks of General Practitioners in The Netherlands

Abstract: One of the major goals of the recent NHS reforms has been to make the NHS more responsive to the needs of patients by offering more choice. DHAs and budget‐holding GP practices have been given an incentive to obtain better value for money in purchasing health care services. In doing so they will have to take account of the existing GP referral patterns for as “key advisers” GPs can have major influence on patients′ choice of hospitals and consultants. Until now not much has been known about the structure, deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, this is only partly the case. Several studies have shown that GPs' preferences are also influenced by their (personal) relationships with consultants [23,24]. Therefore, mutatis mutandis, one could state that for GPs, as for consumers, not only technical aspects count, but also functional aspects.…”
Section: The Relationships With Consumersmentioning
confidence: 99%
“…However, this is only partly the case. Several studies have shown that GPs' preferences are also influenced by their (personal) relationships with consultants [23,24]. Therefore, mutatis mutandis, one could state that for GPs, as for consumers, not only technical aspects count, but also functional aspects.…”
Section: The Relationships With Consumersmentioning
confidence: 99%